2022
DOI: 10.3390/act11030078
|View full text |Cite
|
Sign up to set email alerts
|

Robust Adaptive Control of Knee Exoskeleton-Assistant System Based on Nonlinear Disturbance Observer

Abstract: This study presents a control design of an angular position for the exoskeleton knee assistance system based on a model reference adaptive control (MRAC) strategy. Three schemes of the MRAC design have been proposed: the classical MRAC, MRAC with an adaptive disturbance observer, and MRAC with a nonlinear observer. The stability analysis for each scheme has been conducted and developed based on the Lyapunov theorem to prove the uniform ultimate bound of tracking and estimation errors. In addition, the adaptive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…The Exoskeleton Knee system is a wearable robotic device that is used to restore or enhance the function of the lower limb (Shawgi et al, 2022;Alawad et al, 2022). Figure 1 depicts the geometric representation of leg motion at the knee joint (Aljuboury et al, 2022). According to Figure 1., the parameters đť‘š and đť‘™ are the mass and length of the shank, respectively, while đť‘” is the gravitational acceleration.…”
Section: Modelling Of Exoskeleton System For Lower-limbmentioning
confidence: 99%
See 1 more Smart Citation
“…The Exoskeleton Knee system is a wearable robotic device that is used to restore or enhance the function of the lower limb (Shawgi et al, 2022;Alawad et al, 2022). Figure 1 depicts the geometric representation of leg motion at the knee joint (Aljuboury et al, 2022). According to Figure 1., the parameters đť‘š and đť‘™ are the mass and length of the shank, respectively, while đť‘” is the gravitational acceleration.…”
Section: Modelling Of Exoskeleton System For Lower-limbmentioning
confidence: 99%
“…The nonlinear dynamic for the exoskeleton and human model with one joint, at the knee, is determined through the use of the Euler-Lagrange method. The dynamic modelling of the system can be expressed as follows (Aljuboury et al, 2022;Bkekri et al, 2019;Mefoued,2015) (see Equation ( 1)):…”
Section: Modelling Of Exoskeleton System For Lower-limbmentioning
confidence: 99%
“…The accuracy of gait tracking of exoskeleton system is considerably enhanced and the follow-up performance has been greatly improved. In [24], Aljuboury et al presented the design of three control schemes based on model reference adaptive control (MRAC) for an exoskeleton knee assistance system. This study showed that the observer-based MRAC outperformed the classical MRAC and adaptive MRAC in terms of robustness characteristics and tracking accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…A new control strategy (ADRC) has been used recently to cancel these effects due to the impact of internal and external disturbances on the position trajectory of the Exoskeleton system [9][10][11]. There are numerous ways to build an ADRC, both linear and nonlinear, and the feed-forward controller may use a variety of techniques, including fuzzy control, artificial intelligence control, classical PD, and fractional PD [11][12][13][14][15]. Each of these approaches has benefits and drawbacks in terms of performance robustness against rejection disturbances.…”
Section: Introductionmentioning
confidence: 99%